Pengaruh Kualitas Pelayanan, Komunikasi Pemasaran dan Kepercayaan terhadap Loyalitas Pelanggan Pengguna Shopee - Maria Yasinta Jaghung; Novitawati, Retno Ayu Dewi (Yayasan Lentera Avanya Nagari, 2025)
The purpose of this study is to determine the influence of service quality, marketing communication and trust on customer loyalty of Shopee users in Tlogomas Village, Malang City partially and simultaneously. This study uses a quantitative method. The determination of the sample was determined by the purposive sampling technique so that the research sample was 100 Shopee users in Tlogomas Village, Malang City. The data collection technique used by the researcher is a questionnaire. The data analysis method used is multiple linear regression using the SPSS program. The results of the study prove that service quality has a significant effect on loyalty, marketing communication has a significant effect on loyalty with a t-value of 4.208 and trust has a significant effect on loyalty. The results simultaneously showed that service quality, marketing communication and trust had a significant effect on loyalty. The results of this study can be understood that the existence of good service quality, good marketing communication and trust can increase the loyalty of Shopee users.